Gut metagenomics in relation to diet and methanogenesis in arctic herbivores - Salgado, Alejandro Flores (UiT The Arctic University of Norway, 2017)
Paper III of this thesis is not available in Munin. Paper III: Salgado‐Flores, A., Tveit, A. T., Wright, A. D., Pope, P. B., Sundset, M. A.: “Characterization of the cecum microbiome from wild and captive rock ptarmigans from Svalbard and northern Norway in relation to diet composition”. (Manuscript). Enteric methane (CH4) from gut microbial fermentation of complex organic polymers in ruminants comprises an important source of the anthropogenic CH4 emissions and may also represent a significant loss of metabolic energy to the host animal depending on diet. CH4 is produced by specialized microbes called methanogens. Extensive research exists on enteric CH4 production and methanogens in domestic ruminants, but little is known about arctic herbivores. Reindeer (Rangifer tarandus tarandus), muskox (Ovibos moschatus), and rock ptarmigan (Lagopus muta), typically consume plants rich in toxic plant secondary metabolites (PSMs). PSMs may depress enteric CH4 production in high concentrations. The objective of this PhD project was to characterize the gut microbiome from these animals, with special emphasis on CH4 metabolism and related to diets high in PSMs. Investigating the microbiology of methanogenesis would help better understand their digestive physiology. Molecular biology techniques were used for these studies: quantitative real-time PCR, amplicon sequencing, and shotgun metagenomics. Reindeer fed lichens (high in PSMs) and muskoxen feeding on an autumn pasture presented increased proportions of methanogens (Methanobrevibacter ruminantium and Methanobrevibacter olleyae) that may be related to the low CH4 output previously described for these ruminants. Housing methanogens with expected low CH4 potentials might result in reduced energy losses in reindeer. Other factors apart from high PSMs contents may account for the presence of these methanogens. Rock ptarmigans mostly contained methanol-utilizing methanogens, potentially related to methanol production from pectin degradation. This thesis presents the first ...